2006
DOI: 10.1186/1471-2148-6-98
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: The past decade has seen a remarkable increase in the number of recognized mouse lemur species (genus Microcebus). As recently as 1994, only two species of mouse lemur were recognized according to the rules of zoological nomenclature. That number has now climbed to as many as fifteen proposed species. Indeed, increases in recognized species diversity have also characterized other nocturnal primates -galagos, sportive lemurs, and tarsiers. Presumably, the movement relates more to a previous lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Although some studies suggest that M. murinus preferentially inhabits dry forest habitat in northwestern Madagascar [79], it could be argued that M. murinus is a generalist species as it is often found in both dry deciduous forest and wet, gallery forest habitats in the southeast [38,39]. These habitat associations contrast with M. griseorufus , which is more common in xeric, spiny forest [21,39], though recently M. griseorufus has been shown to inhabit both spiny and gallery forests at the Beza Mahafaly Private Reserve [45]. Therefore, while these habitat preferences may have been important in the original subdivision of the ancestral species, there is no direct evidence supporting the hypothesis that this drove their initial divergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies suggest that M. murinus preferentially inhabits dry forest habitat in northwestern Madagascar [79], it could be argued that M. murinus is a generalist species as it is often found in both dry deciduous forest and wet, gallery forest habitats in the southeast [38,39]. These habitat associations contrast with M. griseorufus , which is more common in xeric, spiny forest [21,39], though recently M. griseorufus has been shown to inhabit both spiny and gallery forests at the Beza Mahafaly Private Reserve [45]. Therefore, while these habitat preferences may have been important in the original subdivision of the ancestral species, there is no direct evidence supporting the hypothesis that this drove their initial divergence.…”
Section: Discussionmentioning
confidence: 99%
“…We also chose data sets with samples covering a large portion of the known geographic range of both species to assemble the most geographically complete data set possible (Figure 1 B; Additional file 1 : Table S1). Although recent studies have suggested that M. murinus may possibly contain at least three undocumented species, [ 43 - 45 ], we treat these populations as M. murinus sensu lato for the purpose of this study. The final data set consisted of the following nuclear loci: alpha enolase intron (ENOL: 916 bp), alpha fibrinogen intron (FIB: 608 bp), von Willebrand factor intron (VWF: 795 bp).…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast to observations at other places. At Beza Mahafaly in southwestern Madagascar, Heckman et al [ 32 ] observed only griseorufus- like mitochondrial haplotypes despite morphological evidence for the presence of both species [ 21 , 56 ]. At Berenty, west of our study area, Yoder et al [ 31 ] observed mitochondrial haplotypes of Microcebus murinus in gallery forests and of M. griseorufus in adjacent spiny bush without admixture.…”
Section: Discussionmentioning
confidence: 99%
“…Microcebus griseorufus is a microendemic in the southern dry spiny bush [21,30-32]. Microcebus murinus has a very large distribution that comprises the western seasonally dry deciduous forest, southern gallery forest and southeastern humid littoral forest [21,30,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation